How to reduce agrifood systems' future hidden costs? A multicountry case study - Getaneh, Yonas; Nigussie, Yirgalem; Abera, Wuletawu; Mulatu, Kalkidan; Balcha, Yodit; Tibebe, Degefie; Eshete, Meron; Mekonen, Bekele; Tamene, Lulseged (2024)
Despite the significant role of agriculture in Ethiopia's economy, the economic damage caused by negative externalities within the agri-food system has been largely unknown due to the intangible nature of these impacts. This research aimed to evaluate the evolution of hidden costs in Ethiopia's agri-food system by leveraging the 2023 FAO-SOFA flagship report through literature review, stakeholder consultation, and FABLE-based modeling. The total hidden costs of Ethiopia's agri-food system were estimated to be 51 billion 2020 PPP dollars per year. The most significant contributor to these hidden costs was the social sector, particularly poverty among agri-food workers, accounting for 24.3 billion 2020 PPP dollars annually. Environmental externalities related to climate change and land-use change were the second-largest contributors, reaching 19 billion 2020 PPP dollars per year. Specific recommendations to reduce hidden costs include a lower population growth path, decreasing livestock numbers, and increasing crop and livestock productivity.